Examining factors for the adoption of silvopastoral agroforestry in the Colombian Amazon - C. O. Alvarado Sandino; A. P. Barnes; I. Sepúlveda; M. P. D. Garratt; J. Thompson; M. P. Escobar-Tello (Scientific Reports, 2023)
Abstract Current land use systems in the Amazon largely consist of extensive conventional productivist livestock operations that drive deforestation. Silvopastoral systems (SPS) support a transition to low carbon production if they intensify in sympathy with the needs of biophysical and socio-economic contexts. SPS have been promoted for decades as an alternative livestock production system but widespread uptake has yet to be seen. We provide a schema of associating factors for adoption of SPS based on past literature in tropical agriculture and apply this to a bespoke survey of 172 farms in the Caquetá region of the Colombian Amazon. We find a number of factors which do not apply to this region and argue for a context specific approach. The impact of managing increased market access and opportunities for SPS producers are crucial to avoiding additional deforestation. Further understanding of the underlying antecedents of common factors, such as perceptions of silvopastoral systems, would reduce the risk of perverse policy outcomes.